Agitated boundaries: non-human creatures and supernaturalism in Colin Cotterill’s Siri Paiboun crime series - Panida Boonthavevej (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article is a study of animals and supernaturalism in the Siri Paiboun crime series, featuring Siri Paiboun, the national coroner of the newly established Lao People’s Democratic Republic. Mainly informed by critical theories of animal studies, the article contends that the animal offers a critical intervention of crime fiction studies. Animals in the series are not just tools or companions to humans, but active agents that, along with preternatural happenings, operate to collapse the distinction between human and non-human animals. Categorised into speaking and gazing animals, fantastic animals, and real and symbolic animals, these animals serve to blur the demarcation line between subjects and objects, physical and spiritual forms, and animals and colonised subjects, respectively. Eventually, the trans-species traffic, witnessed by some of the human characters, results in the de-centring of the anthropomorphic definition of crime. Under supernatural circumstances, animals in this crime series function as a constant reminder that they can suffer like humans, and crime against animals should thus be punishable by law as crime against humans.